2014
DOI: 10.1016/j.cropro.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

European starling feeding activity on repellent treated crops and pellets

Abstract: a b s t r a c tThe varied diet of European starlings (Sturnus vulgaris L.) can present challenges when working with starlings in experimental testing and holding situations and should be taken into account when testing repellents applied to food. Our purpose was to evaluate an anthraquinone-based repellent (Arkion Life Sciences, New Castle, DE, USA; active ingredient 50% 9,10-anthraquinone; hereafter anthraquinone) and SucraShieldÔ (Natural Forces, Davidson, NC, USA; active ingredient 40% sucrose octanoate est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…European starlings offered sweet corn treated with 327–4805 mg AQ kg −1 and untreated sweet corn in a choice test within cages ate similar amounts of AQ‐treated and untreated sweet corn as concentration increased. Whereas birds repelled by anthraquinone would typically increase untreated corn consumption, starlings ate less overall, potentially owing to the high sucrose concentration in sweet corn and starlings' inability to process sucrose …”
Section: Avian Foliar Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…European starlings offered sweet corn treated with 327–4805 mg AQ kg −1 and untreated sweet corn in a choice test within cages ate similar amounts of AQ‐treated and untreated sweet corn as concentration increased. Whereas birds repelled by anthraquinone would typically increase untreated corn consumption, starlings ate less overall, potentially owing to the high sucrose concentration in sweet corn and starlings' inability to process sucrose …”
Section: Avian Foliar Treatmentsmentioning
confidence: 99%
“…In European starling cage testing with blueberries ( Vaccinium spp. ), 5000 mg AQ kg −1 was not sufficient to deter feeding, although untreated blueberries were preferred over blueberries treated with 2500 mg AQ kg −1 in choice tests . An additional foliar application of AQ involves protection of nut crops from crow damage.…”
Section: Avian Foliar Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for small birds like robins and tomtits that peck at bait, surface coating might provide greater protection as the repellent would be concentrated in the outer layers of the bait. Tupper et al (2014) found that anthraquinone was effective at repelling European starlings (Sturnus vulgaris) when applied topically to a pellet matrix but not when incorporated into the pellet matrix even at a much higher concentration. However, the increased costs involved in surface coating may be an issue.…”
Section: Strategies For Repellent Testing and Usementioning
confidence: 99%
“…Despite the potential advantages such structured approaches may offer (Clark 1998) and new insights into the responses of birds to sensory cues (Clark 2014;Werner et al 2014), most of the recently published experimental trials of bird repellents internationally have focussed on further testing or enhancement of a few reasonably well characterised compounds, particularly anthraquinone, d-pulegone, and methyl anthranilate (e.g. Carlson et al 2013;Esther et al 2013;Tupper et al 2014;Werner et al 2015). The main reason for this appears to be a focus on repellents that are already registered for use, given the very high cost of registering novel products (Eisemann et al 2011).…”
Section: Strategies For Repellent Testing and Usementioning
confidence: 99%